Characterization of rice noodles fortified with different levels of stabilized rice bran - Mohamad, A.; Shah, N.N.A.K.; Sulaiman, A.; Adzahan, N.M.; Aadil, R.M. (Rynnye Lyan Resources, 2024)
The study aimed to evaluate the effects of stabilized rice bran (SRB) on the functional, physicochemical, nutritional, and sensory characteristics of rice noodles. This study assessed the influence of SRB on the cooking quality and functional and nutritional properties of rice noodles. A total of five different levels of SRB (0, 2, 5, 10, and 15% w/ w) were incorporated into the rice noodles. Compared to control rice noodles (0% SRB), those incorporating 10 and 15% SRB demonstrated significant differences (p < 0.05) in cooking time (CT) and cooking loss (CL). As the level of SRB increased, the water absorption index (WAI), water solubility index (WSI), hardness, adhesiveness, springiness, and chewiness values of rice noodles decreased, respectively. The incorporation of SRB influenced (p < 0.05) the colour, proximate constituents (moisture, ash, carbohydrate, protein, fat, and crude fibre), antioxidant activity, and total phenolic contents of rice noodles. Noodles with 10% SRB showed the highest score for overall acceptability (7.86±1.14), while noodles with 15% SRB received the lowest score (6.31±0.81) in all sensory elements tested. Therefore, SRB can be used as a functional ingredient to enhance the nutritional and physicochemical properties of rice noodles with improved acceptability